Knowledge, Attitude and Perception of Pregnant Women towards Hepatitis E - Jibran Umar Ayub, Azhar Zahir Shah, Umar Ayub Khan, Ayesha Gul, Faheem Naeem Awalzai, Zainub Akhtar, Assad Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatitis E is one of the most common diseases during pregnancy which can cause increased mortality and devastating complications. Objective: To assess the knowledge, attitudes and perceptions of Pregnant Women towards Hepatitis E Materials and Methods: This cross sectional study was conducted in Maqsood Medical Complex General Hospital for a duration of six months. The sampling technique was non probability convenient sampling. The inclusion criteria were pregnant women in first trimester aged between18 and 45 years. Patients with molar pregnancy and those having history of gastrointestinal disorders were excluded from the study. A total of 100 patients were taken Results: Among women 80% heard about Hepatitis E, 81% known a person ever infected with viral infection, 60% don’t know that this infection was caused by virus, only 46% reported that they knew that It was transmitted through contaminated food and water, 56% reported that they knew it was transmitted by blood transfusion, 54% reported that they knew it can be transmitted sexually, 45% knew that it can be transmitted from mother to fetus, 61% reported that they knew that Hepatitis E is more dangerous in pregnancy, only 26% reported that they knew it can cause hepatic failure and only 38% reported that they knew there is vaccination of Hepatitis E. Questions regarding attitude of women towards Hepatitis-E showed that only 45% reported that they were at risk of getting Hepatitis-E infection Conclusion: From the above results one can conclude that there was good awareness of hepatitis E among pregnant women, yet there is a need for more health education and vaccination drive to reduce its mortality. Keywords: Hepatitis E, Pregnancy